Harnessing digital technology to foster inclusive women entrepreneurship in post-conflict Northern Province, Sri Lanka: Opportunities, barriers, and impact - Shivany, S.; Priya, M. (Shanlax Publications, 2026)
This qualitative inquiry explores the function of digital technologies in promoting inclusive entrepreneurial ventures among women in the post-conflict Northern Province of Sri Lanka. Acknowledging the region's distinct socio-economic challenges and cultural context, the research adopts a case study methodology to investigate how female entrepreneurs leverage digital resources to surmount obstacles, gain access to opportunities, and bolster their economic and social agency. The study concentrates on micro, small, and medium-sized enterprises across diverse sectors, including agriculture, retail, textiles, and services. Employing a combination of purposive and snowball sampling techniques, 15–20 women entrepreneurs from various districts within the province were recruited, alongside key informants such as government officials, representatives from women’s organizations, and experts in digital inclusion. Data were gathered through semi-structured, in-depth interviews conducted in Tamil or Sinhala, yielding comprehensive insights into participants’ experiences regarding the adoption of digital technology. The results indicate that digital technologies offer notable advantages, such as enhanced market reach, improved business visibility, and greater operational effectiveness. Interviewees also reported gains in financial autonomy and increased involvement in household and community decision- making processes. Nevertheless, the research also exposed ongoing challenges, including low levels of digital literacy, elevated internet expenses, inadequate infrastructure, and socio-cultural impediments to women’s public and entrepreneurial activities. The perceived lack of cohesive and contextually relevant institutional assistance was also noted. The study posits that although digital technologies present significant opportunities for female entrepreneurs in the Northern Province of Sri Lanka, their successful integration necessitates interventions tailored to the local context. These encompass community-based digital literacy initiatives in local languages, affordable infrastructure, culturally appropriate engagement approaches, and strong collaborations between the public and private sectors. The research highlights the importance of policymakers and development organizations in creating inclusive support mechanisms that address the convergence of gender, post-conflict recovery, and technology. Recognizing the constraints associated with its geographic focus and qualitative nature, the study advocates for more extensive and longitudinal research to assess the sustained effects of digital entrepreneurship on women’s empowerment.
Keywords: Women entrepreneurship; Digital technology; Post-conflict development; Northern province; Sri Lanka; Socio-cultural barriers; Digital inclusion